Performance analysis of a novel-designed building roof top photovoltaic/ thermal collector under partial shading conditions - Cosanay, Hakan; Öztop, Hakan Fehmi; Ozalp, Coskun; Sahin, Ibrahim H.; Hurdogan, Ertac; Sahin, Ahmet Z. (Pergamon-Elsevier Science Ltd, 2025)
A numerical study has been performed in this paper to investigate the effect of shading on the performance of novel-designed photovoltaic/thermal (PV/T) systems, focusing on both thermal and electrical outputs. Six different shading scenarios are simulated through computational analysis to examine their effects on the efficiency of PV/T collectors, considering different water duct shapes and shading positions. The finite volume technique is used to simulate the system and MATLAB Simulink is used to evaluate the efficiency. The decreasing in the heat transfer coefficient is analyzed under shading, with the lowest values occurring for certain shading positions and duct inclinations. It is found that the heat transfer coefficient (HTC) decreases with increasing shading area across all duct inclination angles. The impact of shading on outlet water temperature is also evaluated and found to be small due to stored thermal energy and low shading area ratios. In addition, the output power comparisons illustrate the importance of water duct shape and shading parameters, with considerable variations observed in output power based on shading area and position. The results of this investigation are expected to provide valuable insights into optimizing PV/T system performance under shading conditions, highlighting the significance of shading mitigation strategies for enhanced energy output. The findings highlight the critical impact of shading on PV/T system performance, particularly in reducing heat transfer efficiency and electrical output. The results emphasize the importance of optimizing water duct design and implementing shading mitigation strategies to enhance overall system efficiency. The study also suggests that while shading has a minor effect on outlet water temperature due to thermal storage, it significantly influences power generation, making strategic panel placement essential for maximizing energy output.
Keywords: Shading effect; PV/T collectors; Numerical analysis; Solar energy; Electricity